Manfaat Sekuen Genom Lengkap dalam Identifikasi Gen: Peranan Kelompok Gen Actin-myosin dalam Sistem Pertahanan Tanaman - Reflinur Reflinur; Dwinita Wikan Utami (Jurnal AgroBiogen, 2005)
Complete genome sequencing of Arabidopsis thaliana and rice (Oryza sativa) were accomplished in 2000 and 2004, respectively. The availability of high quality genome sequences of A. thaliana and rice amenable for identification and understanding of the structure and functional genes in the plant genome. One of the genes family that have been investigated is the actin-myosin genes. This genes family contributes to signalling process of the plant defence mechanism. This paper focuses on phylogenetic characterization and activation of actin-myosin genes family with emphasis on involvement on the plant defence mechanism.